Prevalence of dyslipidemia and associated factors in sedentary occupational population from Shanghai: a cross-sectional study - Dongxing Gu; Dandan Wang; Qinzhong Zhu; Li Luo; Tiantian Zhang (BMC, 2024)
Abstract Background Dyslipidemia is a major risk factor for cardiovascular diseases, but its prevalence and determinants among sedentary occupational population are poorly understood. This study aimed to investigate the prevalence and associated factors for dyslipidemia among a sedentary occupational population in Shanghai, China. Methods We collected data from 35,950 sedentary occupational workers on their demographics, social, medical, and family history, lifestyle, anthropometry, and biochemistry. We used the 2016 Chinese guideline for the management of dyslipidemia in adults to define dyslipidemia and its subtypes. We performed multivariate logistic regression to examine the factors associated with dyslipidemia. Results The prevalence of dyslipidemia was 29.10%, with 15.86% for high triglycerides (TG), 6.43% for high total cholesterol (TC), 5.37% for high low-density lipoprotein cholesterol (LDL-C), and 14.68% for low high-density lipoprotein cholesterol (HDL-C). Men had a significantly higher prevalence of dyslipidemia than women (39.64% vs. 12.43%, P < 0.01). Factors associated with dyslipidemia included older age, being married, longer sedentary time while resting, frequent intake of animal viscera, current smoking, hypertension, diabetes, and obesity. Current drinking was associated with a 1.24 times higher prevalence of high TG (P < 0.01). Current smokers were less likely to have low HDL-C than non-smokers. Conclusions Our present study, in a population of 35,950 sedentary occupational workers from Shanghai, demonstrated a prevalence of dyslipidemia, but lower than in other previous studies without the limitation of occupational characteristics. Prevention and control measures for dyslipidemia should take into account the characteristics and related factors for this population group.